Water quality monitoring using lowcost digital camera / Ernieza Suhana Mokhtar - Mokhtar, Ernieza Suhana (2008)
Water quality describes the physical, chemical and biological characteristic of water that relates to human and nature life. Water quality parameters consist of Total Suspended Solids (TSS), turbidity, Secchi Disk Depth (SDD), temperature and colour. Example of factors affecting the quality of water bodies (i.e. lakes and reservoirs) are urban runoff, solid waste and soil erosion. Several methods i.e. conventional method, satellite remote sensing method, and digital camera method can be used to determine water quality parameters. Conventional method involves collecting water sample and laboratory analysis. This method is time consuming and not efficient to represent water quality of large area. Satellite remote sensing techniques using various sensors i.e. Landsat, Moderate Resolution Imaging Spectroradiometer (MODIS), IKONOS and Tiungsat-1 can be used to assess several water quality parameters (i.e. TSS, turbidity, chlorophyll and SDD) on large area coverage. Although this method can be used to monitor water quality of large area, image acquisition and data processing are costly and time consuming. A number of studies have utilized digital cameras to determine the water quality parameters; the results are still not conclusive. The aim of this study is to access the potential use of low-cost digital cameras in water quality assessment.